Preparation of WO3/Mo/CrNi/TiO2 Composite Multifunctional Photothermal Conversion Films With Self-Cleaning and Low Emissivity - Cheng, Wenqing; Ren, Huixue; Chen, Yanxue; Wu, Daoji; Zhang, Shuai; Yu, Chunfeng; Li, Fangjun (Frontiers in Energy Research, 2022)
In order to improve the sunlight transmittance and infrared reflectivity, different membrane compositions are designed to realize self-cleaning and low-infrared-transmittance of the membrane. The WO3/Mo/CrNi/TiO2 composite film was prepared by magnetron sputtering technology, and the complementary effect of these different film thickness was analyzed. The microstructure characterization proves that the self-cleaning function of the composite film is determined by the photocatalytic properties and superhydrophilic properties of the TiO2.